Metabolic Insights into Male Fertility: A Narrative Review of the Role of Adiponectin on the Hypothalamic–Pituitary–Testicular Axis - Gabriel, Ana Luiza Romano [UNESP]; Fioretto, Matheus Naia [UNESP]; Barata, Luisa Annibal [UNESP]; Justulin, Luis Antonio [UNESP]; Felisbino, Sergio Luis [UNESP] (Oxford University Press (OUP), 2025)
Adiponectin (APN), an essential adipokine with metabolic and anti-inflammatory properties, is increasingly being recognized as a central regulator of male reproductive health. Acting across multiple levels of the hypothalamic–pituitary–gonadal (HPG) axis, APN modulates gonadotropin release, Leydig cell activity, and testosterone synthesis. Dysregulation of this adipokine has been linked to impaired spermatogenesis, testicular dysfunction, and alterations in male accessory organs, ultimately contributing to infertility. Beyond its gonadal effects, the systemic effects of APN, including its roles in insulin resistance and chronic inflammation, further destabilize the hormonal and reproductive landscapes. This narrative review, which is based on studies published between 2008 and 2025, highlights the intricate interplay between APN and testosterone and emphasizes the clinical relevance of this interplay. A deeper understanding of this axis may clarify the metabolic–reproductive connection and open new therapeutic avenues for the management of male infertility in metabolically challenged patients. Graphical Abstract

Adiponectin (APN), an essential adipokine with metabolic and anti-inflammatory properties, is increasingly being recognized as a central regulator of male reproductive health. Acting across multiple levels of the hypothalamic-pituitary-gonadal (HPG) axis, APN modulates gonadotropin release, Leydig cell activity, and testosterone synthesis. Dysregulation of this adipokine has been linked to impaired spermatogenesis, testicular dysfunction, and alterations in male accessory organs, ultimately contributing to infertility. Beyond its gonadal effects, the systemic effects of APN, including its roles in insulin resistance and chronic inflammation, further destabilize the hormonal and reproductive landscapes. This narrative review, which is based on studies published between 2008 and 2025, highlights the intricate interplay between APN and testosterone and emphasizes the clinical relevance of this interplay. A deeper understanding of this axis may clarify the metabolic-reproductive connection and open new therapeutic avenues for the management of male infertility in metabolically challenged patients.